Model PLTA Skala Kecil dengan Generator DC 24 Volt - Yeskiel Astara; Aries Boedi Setiawan; Wahyu Dirgantara (Pusat riset dan Inovasi Nasional, 2025)
Small-scale Hydropower Plants (HPP) are an effective renewable energy alternative to meet electricity needs in remote areas. This study aims to develop and test a small-scale HPP model using a 24-volt DC generator as the main component. The development process involves analyzing water flow rates, head height, and the conversion of mechanical energy into electrical energy. The 24-volt DC generator was chosen due to its availability, high efficiency, and ease of integration with energy storage systems.This small-scale HPP model is expected to provide a reliable electricity solution for households or small communities, particularly in areas not yet connected to conventional power grids. This study also paves the way for further development, especially in optimizing design and utilizing more efficient components. With a generator capacity of 24 volts, the voltage produced will tend to be stable compared to a generator with a capacity of 12 volts. So that this study is able to provide an accurate impact given by the water discharge that drives the.